Uniform regularity for the isentropic compressible magneto-micropolar system - Fan, Jishan; Wang, Peng; Zhou, Yong (Mathematical Modelling and Analysis, 2021)
In this paper, we are concerned with the uniform regularity estimates of smooth solutions to the isentropic compressible magneto-micropolar system in . Under the assumption that , and by applying the classic bilinear commutator and product estimates, the uniform estimates of solutions to the isentropic compressible magneto-micropolar system are established in space, .